Identifying Teachers’ Strategies in Teaching Reading Comprehension - Aminah, Suci; Sukma, Fitri Alya Okta (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
This study aimed to analyze the strategies used by teachers of English in teaching reading comprehension at SMP Islam Al-Fahd Palembang. This type of research was qualitative. The research instruments were an observation checklist and interviews. The subjects of this study were two teachers of English having experience teaching English for more than five years and being certified. The results of the study found that two strategies were used by the teacher in teaching reading comprehension, namely Scaffolding and QARs (Question-Answer Relationships). With a scaffolding strategy, teachers of English can develop the ideas that students have about reading comprehension. With QARs (Question-Answer Relationships), teachers of English can determine how well their students understand what the teacher has given them. Furthermore, this study would help teachers of English improved at teaching English, especially reading comprehension because this study discussed teacher strategies for teaching reading comprehension.